The development of critical thinking, team working, and communication skills in a Business School – a project-based learning approach - Dias-Oliveira, Eva (2024)
This study presents a Project-Based Learning (PBL) approach – the Multidisciplinary Project I course (MPI) - conceived to improve critical thinking skills of first-year business students while also mobilising teamwork and communication skills. The main goals are to 1) describe the methodological PBL approach of MPI and 2) analyse changes in critical thinking, team working, and communication skills during the semester (pre- and post-test) by comparing management and economics students enrolled in MP1 (n = 946) to a control group (n = 210) including students from other courses. Our findings show that, at the end of the semester, MPI students reported a greater reduction in their critical thinking difficulties and communication apprehension and improvements in teamwork skills. This study provides evidence supporting the inclusion of PBL approaches to promote skills in business students that can be transferable to real-world settings.